Dynamic strength analysis of the key components of the beam-type pumping unit with dynamic tracking balance - Bo Wang; De-Chun Chen (Fracture and Structural Integrity)
Aiming at the shortages of large reversing impact, high energy consumption and poor balance effect of conventional beam-type pumping unit, the design scheme of beam-type pumping unit with dynamic tracking balance is proposed. The load-displacement curves from on-site trial shows that the pumping with dynamic tracking balance has a better effect of load balance, and a high production and power efficiency. According to the designed structure, the dynamic responses of the beam and connecting rods are analyzed. The results show that the maximum Von Mises stresses in the beam and connecting rods are 36.96 MPa and 27.83 MPa, respectively. The key components of designed beam-type pumping unit with dynamic tracking balance meet the requirement of strength.